A bibliometric analysis of research on pediatric preoperative anxiety (2007–2022) - Zhong, Yue; Gong, Huishu; Long, Feiyu; Zhou, Xingchen; Zhou, Jun; Wang, Maohua; Peng, Tao (Frontiers in Pediatrics, 2024)
This study aimed to analyze the current state of research on preoperative anxiety in children through CiteSpace, VOSviewer, and the identification of hot spots and frontiers.Relevant data were retrieved from the Web of Science Core Collection using the search terms children and preoperative anxiety. Data were analyzed using VOSviewer (version 1.6.18), CiteSpace (5.7. R5) software, and Scimago Graphica.A total of 622 articles were published between 2007 and 2022, with an increasing trend over time. Kain, Zeev N. (13;2.09%) and Dalhousie University (15; 2.41%) were the most influential authors and most prolific institutions, respectively. The United States (121; 19.45%) was the country with the most publications. Pediatric anesthesia (55; 8.84%) had the most publications.High-frequency keywords were categorized into three themes, including nonpharmacologic interventions for preoperative anxiety in children, preoperative medications, and risk factors for anxiety; of these, "predictor" (38; 2016) and "sedative premedication" (20; 2016) were the most studied keywords over the past 6 years. "Distraction" (67; 2019) and "dexmedetomidine" (65;2019) have been the main areas of interest in recent years.Research on preoperative anxiety in children has been the focus of increasing attention over the past fifteen years, with the majority of publications from high-income countries. This review provides a useful perspective for understanding research trends, hot topics, and research gaps in this expanding field.